PENGARUH CUSTOMER EXPERIENCE TERHADAP BEHAVIORAL INTENTION WISATAWAN DI SAUNG ANGKLUNG UDJO (Survey Terhadap Wisatawan Nusantara yang Berkunjung ke Saung Angklung Udjo) - Rahmi, Mildayani; Andari, Rini; Yuniawati, Yeni (Universitas Pendidikan Indonesia, 2016)
Saung Angklung Udjo is one of the tourist destinations in Bandung city, which has a complete cultural workshop contains performances, handicraft centers of bamboo and bamboo musical instrument workshop. Tourist of Saung Angklung Udjo comes from outside West Java even abroad. The researcher did a pre-research to Indonesian tourists on their behavioral intention at Saung Angklung Udjo. The result indicated that there was low intention to visit the destination. Saung Angklung Udjo provides a different experience to tourists, which implementing a customer experience strategy that consists of the physical environment and social interaction. The purpose of this study was to obtain findings on customer experience as the independent variable which consists of the physical environment and the social interaction. Moreover, the behavioral intention as a dependent variable which consists of repurchase intention, premium price and word of mouth were studied. The type of research was a descriptive and verification, using a questionnaire as the instrument that distributed to 100 respondents through systematic random sampling technique. The data were analysed using a multiple regression techniques. The results indicated that there was a partial and simultaneous influence of customer experience for the tourist behavioral intention. The physical environment resembled in the musical instrument was perceived as a high value by the respondents. The hospitality of the employee as the social interaction dimension has also perceived well by the respondents.